Press Release Nescafe Ice Roast Hadir Temani Para Pecinta Musik di Pestapora 2024 - Vega Ayunda Aditama; Elizabeth Shinta Gunawan; Daris Nabil Firdausy; Marjam Desma Rahadhini (Comit: Communication, Information and Technology Journal, 2025)
This study discusses the press release in the launch of the new product Nescafe Ice Roast at the big music event Pestapora 2024. With a qualitative descriptive approach and case study, this study analyzes the Nescafe Ice Roast press release based on the theory and practice of Press Release. The launch of this product took advantage of the momentum of the music festival to increase brand visibility and awareness, targeting the younger generation who like cold coffee. Through strategic collaboration with music festivals, interactive activities, and the use of mass media, Nescafe succeeded in creating direct engagement with the audience and strengthening the brand image as a pioneer in instant coffee innovation. This study shows that this press release meets the elements of an effective press release, such as the inverted pyramid, 5W + 1H, and the SOLAADS approach, and successfully supports brand positioning in the market.